EVALUATION OF EAR AMPUTATION TECHNIQUES AND RESULTS IN DOGS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examined the methods of performing ear amputation in dogs and the process of postoperative recovery. Amputation surgery is a complex process in which dogs are selected based on their ear anatomy, age, degree of injury, and general condition. During the study, various methods such as classical incision, Vshaped incision, lobe (lateral oblique base), and cosmetic amputation were used, regularly observing the postoperative recovery process, decreased inflammatory symptoms, bleeding, and risk of infection.